Status and determinants of intra-household food allocation in rural Nepal - Harris-Fry, Helen A.; Paudel, Puskar; Shrestha, Niva; Harrisson, Tom; Beard, B. James; Jha, Sonali; Shrestha, Bhim P.; Manandhar, Dharma S.; Costello, Anthony M. D. L.; Cortina-Borja, Mario; Saville, Naomi M. (European journal of clinical nutrition, 2018)
Background/objectives Understanding of the patterns and predictors of intra-household food allocation could enable nutrition programmes to better target nutritionally vulnerable individuals. This study aims to characterise the status and determinants of intra-household food and nutrient allocation in Nepal. Subjects/methods Pregnant women, their mothers-in-law and male household heads from Dhanusha and Mahottari districts in Nepal responded to 24-h dietary recalls, thrice repeated on non-consecutive days ( n = 150 households; 1278 individual recalls). Intra-household inequity was measured using ratios between household members in food intakes (food shares); food-energy intake proportions (‘food shares-to-energy shares’, FS:ES); calorie-requirement proportions (‘relative dietary energy adequacy ratios’, RDEARs) and mean probability of adequacy for 11 micronutrients (MPA ratios). Hypothesised determinants were collected during the recalls, and their associations with the outcomes were tested using multivariable mixed-effects linear regression models. Results Women’s diets (pregnant women and mothers-in-law) consisted of larger FS:ES of starchy foods, pulses, fruits and vegetables than male household heads, whereas men had larger FS:ES of animal-source foods. Pregnant women had the lowest MPA (37%) followed by their mothers-in-law (52%), and male household heads (57%). RDEARs between pregnant women and household heads were 31% higher (log-RDEAR coeff=0.27 (95% CI 0.12, 0.42), P < 0.001) when pregnant women earned more or the same as their spouse, and log-MPA ratios between pregnant women and mothers-in-law were positively associated with household-level calorie intakes (coeff=0.43 (0.23, 0.63), P < 0.001, per 1000 kcal). Conclusions Pregnant women receive inequitably lower shares of food and nutrients, but this could be improved by increasing pregnant women’s cash earnings and household food security.